Late toxicity in long-term survivors from a phase 2 study of concurrent radiation therapy, temozolomide and valproic acid for newly diagnosed glioblastoma. Issue 4 (16th April 2018) - Krauze, Andra V; Mackey, Megan; Rowe, Lindsay; Chang, Michal G; Holdford, Diane J; Cooley, Theresa; Shih, Joanna; Tofilon, Philip J; Camphausen, Kevin
Abstract: Background: Valproic acid (VPA) is an antiepileptic agent with histone deacetylase inhibitor activity shown to enhance overall survival and progression free survival in patients with newly diagnosed glioblastoma (GBM). This reports on the late toxicity of the VPA/radiotherapy (RT)/temozolomide (TMZ) combination in the long-term survivors of a phase 2 study evaluating this regimen. Methods: 37 patients with newly diagnosed GBM were initially enrolled on this trial and received combination therapy. VPA/RT/TMZ related late toxicities were evaluated in the 6 patients that lived greater than 3 years using the Cancer Therapy and Evaluation Program Common Toxicity Criteria (CTC) Version 4.0 for toxicity and adverse event reporting as well as the RTOG/EORTC Radiation Morbidity Scoring Scheme. Results: The median duration of follow-up for these 6 patients was 69.5m. In this cohort, the median OS was 73.8m (60.8–103.8m) and median PFS was 53.1m (37.3 – 103.8m). The most common late toxicity of VPA in conjunction with RT/TMZ were the CTC classifications of neurological, pain, and blood/ bone marrow toxicity and most were grade 1/2. There were only two grade 3/4 toxicities. Conclusions: The addition of VPA to concurrent RT/TMZ in patients with newly diagnosed GBM was well tolerated with little late toxicity. Additionally, VPA may result in improved outcomes as compared to historical data and merits further study.